Misoperation analysis of steady-state and transient methods on earth fault locating in compensated distribution networks. (September 2018) - Pandakov, Konstantin; Høidalen, Hans Kristian; Marvik, Jorun Irene
Abstract: Earth fault detection and location are very important issues in distribution networks. Current methods for faulty feeder selection are based on measurements of steady-state or transient signals. The work presented here identifies and gives analyses of scenarios when ground protection based on these methods is prone to misoperation in resonance grounded systems. It is shown that the traditional watt-metric approach can malfunction depending on network and fault parameters. The admittance methods help to eliminate many issues, however they might have complex settings depending on network configurations. Special attention is paid to approaches based on transient signals as the most promising alternative solution. The current work considers methods utilizing zero sequence current, angle, power, energy and admittance transients. The paper reveals limitations for their application mainly due to presence of electrostatic asymmetry, cables in a network, fault resistance and inception angle. Nevertheless, dependability of these methods is higher than the steady-state especially for intermittent faults. It is also found that analysis of prefault information is important both for the steady-state and the transient methods. The obtained results can be used to enhance reliability of protective schemes and as drivers for further developments of new algorithms.